Legal Analysis of Tengkawang Seed Exports in the Context of Natural Resource Conservation - Sanni, Devi Mutiara; Hariri, Achmad (Universitas Internasional Batam, 2024)
The conflict between the Regulation of the Minister of Environment and Forestry (LHK) No. P.106/MENLHK/SETJEN/KUM.1/12/2018 and the Regulation of the Minister of Trade (Permendag) No. 44 of 2012 has created significant legal uncertainty regarding the protection and trade of tengkawang seeds in Indonesia. The LHK Regulation does not include tengkawang seeds as a protected plant species, while the Permendag prohibits the export of tengkawang seeds. This study aims to analyze the normative conflict related to the regulations governing the export of tengkawang seeds and its implications for environmental conservation and the economy in Pontianak City. The research methodology used is normative analysis with a statutory approach. Legal materials were obtained through document studies of laws and regulations and literature reviews.The research results show that this regulatory conflict hinders the export of tengkawang seeds, harms business actors, and potentially increases illegal trade activities. Furthermore, this inconsistency also causes confusion among law enforcement officials and the general public regarding the protection status of tengkawang seeds. This study recommends harmonizing regulations between the Ministry of Environment and Forestry and the Ministry of Trade to ensure effective protection of tengkawang seeds while supporting economic growth through legal and regulated trade. Additionally, in accordance with the legal principle lex posterior derogat legi priori, the newer law should prevail. Moreover, as per the LHK regulation, tengkawang seeds are not classified as protected plant varieties, which legally allows them to be exported.